The subject–symbolic approach to psychological support practice with children and adolescents - Polyakov, A.M. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
The subject-symbolic approach is grounded in cultural-historical theory and addresses a critical gap in the field of psychological support for children and adolescents. It offers a framework for overcoming emotional, behavioral, interpersonal, and self-related difficulties in individuals with typical development as well as those with mild developmental deviations, while also providing support for their caregivers. The approach integrates assistance in resolving these issues with the broader developmental tasks of the child. Its central premise is that psychological support should aim to foster the child's subjectivity and consciousness by restructuring subject-subject relationships and interactions with their immediate social environment, taking into account age-specific and individual characteristics. Transformational change is made possible through the awareness of the symbolic meaning embedded in experience (perezhivanie). A symbol is understood as a cultural form that mediates subject-subject relationships and their representation in individual consciousness. The paper proposes original techniques for joint work with children and their parents, based on the use of symbolic forms. Субъектно-символический подход основан на культурно-исторической теории и восполняет пробел в оказании психологической помощи, направленной на преодоление эмоциональных, поведенческих проблем, проблем межличностных отношений и взаимодействия, самоотношения у детей и подростков с нормотипичным развитием и легкими отклонениями в развитии, а также для оказания помощи их родителям. Подход совмещает помощь в преодолении данных проблем и решении задач психического развития ребенка. Основная идея подхода заключается в направленности помощи на развитие субъектности и сознания ребенка за счет перестройки его субъект-субъектных отношений и взаимодействия с ближайшим окружением с учетом его возрастных и индивидуальных особенностей. Изменения обеспечиваются благодаря осознанию смыслового содержания переживания, выраженного в символической форме. Символ понимается как культурная форма опосредствования субъект-субъектных отношений и их представленности в сознании индивида. Предлагаются оригинальные методы совместной работы с ребенком и его родителями, основанные на использовании символических форм.